Proceedings of the 2004 IEEE International Conference on Control Applications, 2004.
DOI: 10.1109/cca.2004.1387248
|View full text |Cite
|
Sign up to set email alerts
|

Attitude control of a tethered space robot by link motion under microgravity

Abstract: A tethered space robot, which is connected to a mother spacecraft through a peace of tether, is a new space

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Therefore, the requirement for thrust force can be estimated based on the desired tether attitude and system parameters in deployment, according to equations (29) and (31). It is clear that the control torque of the thrusters should be greater than the magnitude of the coupling torque M t .…”
Section: Tether and Attitude Control With Thrustersmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the requirement for thrust force can be estimated based on the desired tether attitude and system parameters in deployment, according to equations (29) and (31). It is clear that the control torque of the thrusters should be greater than the magnitude of the coupling torque M t .…”
Section: Tether and Attitude Control With Thrustersmentioning
confidence: 99%
“…28 Propulsion at the tether tip is also discussed to correct severe disturbances. 29 Most of previous studies give an emphasis on the dynamics and control problem of long tether systems as tens of kilometers. Short tethered systems, on the order of tens of meters, have attracted research interests in space operations [30][31][32] in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nohmi [4][5][6] investigated the arm link to control the TSR's attitude during the deployment phase, and a microgravity experiment was conducted to validate the feasibility of this scheme. Godard [7] designed a nonlinear optimal controller using an inverse optimal technique to control the attitude of a satellite via tether offset variations.…”
Section: Introductionmentioning
confidence: 99%
“…Nohmi et al (Nohmi et al, 1998;Nohmi, 2004;Takehara et al, 2008;Nohmi et al, 2007;Nohmi et al, 2010) employed a mechanism with an arm on subsatellite to create tether tension torque. Microgravity experiments showed that the rotation motion can be suppressed by the tether tension torque.…”
Section: Introductionmentioning
confidence: 99%